Funeral rites: a reflection of the afterlife in ancient Greek and Yoruba traditional belief (2012)
The anxiety regarding the afterlife and immortality has been with man since the dawn of civilization. The question of afterlife is the most important personal question that can be asked in the light of the realization of one’s own mortality. The Afterlife is a generic term for a continuation of existence after death. But the form which an unending or indefinitely human life would take is obscure. However, it is generally believed that the souls of the departed persons make a journey to a specific region or plane of existence. The idea that there can be some continuation in existence after death manifests in religious and traditional beliefs, as well as in the actions and practices of the living, like funerary practices, ancestor worship, the concept of divine judgment, the doctrine of reward and punishment for the soul and the concept of the living-dead. This paper has as its task to examine how funeral rites reflect the concept of afterlife as a philosophical and religious belief among the ancient Greeks and the Yoruba of Nigeria